(untitled) (Iranian Journal of Kidney Diseases, 2015)
Introduction. Soluble major histocompatibility complex class I chain-related antigen A (soluble MICA) has recently been considered as an inhibitory molecule which is shed from tumors and protects them against natural killers and some subgroups of T cells’ cytolysis. In transplantation, soluble MICA is also a foreign antigenic molecule that can induce allospecific responses. This study aimed to clarify its possible role in long-term kidney allograft outcome. Materials and Methods. Thirty patients with biopsy-proven chronic allograft dysfunction (CAD) were pair-matched with kidney allograft recipients with 30 stable graft function. Fifteen healthy individuals were enrolled as controls. Soluble MICA antigen and anti-HLA antibodies were measured in their serum. Results. There was no significant difference between CAD patients, stable recipients, and healthy volunteers in frequency or titer of soluble MICA; however, soluble MICA-positive patients were more frequent in the stable group was than the CAD group (43.4% versus 33.3%). In addition, a high level of soluble MICA was accompanied by enhanced humoral responses. No significant difference was found in anti-HLA antibodies production between the CAD and stable groups. Conclusions. Our data suggest that soluble MICA, at least in a defined range, can protect the allograft against natural killers and T cell cytolysis; nonetheless, its excessive amounts might stimulate immune system to exert enhanced humoral response. In order to confirm the protective or detrimental role of soluble MICA in kidney transplantation, conducting larger studies is necessary.